2013
DOI: 10.4161/cc.26868
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms potentially associated with response to metformin in postmenopausal diabetics suffering and not suffering with cancer

Abstract: Metformin is a well-known antidiabetic medication, which, besides diabetes, may be involved into modulation of other age-related pathologies, including cancer. The study concerns 12 gene polymorphisms divided into 2 groups consisting of 6 genes each. The first group was composed from so-called "standard" (S) polymorphisms, for which the connection with metabolic response to metformin is already established. The second group included polymorphisms of genes encoding proteins possibly connected with diabetes mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
9
0
4
Order By: Relevance
“…Another study confirmed pro-apoptotic properties of metformin treatment at near-pharmacological levels (60 µmol/L), which acted by induction of proapoptotic genes and increased apoptosis of HCT116 cell line [30]. The effectiveness of metformin may be associated with a genetic polymorphism in patients with diabetes [31]. Only one study did not confirm the ef-fect of metformin used alone on inhibition of cell proliferation and induction of apoptosis in 3 CRC cell lines treated with 3 concentrations of metformin (1, 5, and 10 mmol/L) [32].…”
Section: Cell Line Studiesmentioning
confidence: 67%
“…Another study confirmed pro-apoptotic properties of metformin treatment at near-pharmacological levels (60 µmol/L), which acted by induction of proapoptotic genes and increased apoptosis of HCT116 cell line [30]. The effectiveness of metformin may be associated with a genetic polymorphism in patients with diabetes [31]. Only one study did not confirm the ef-fect of metformin used alone on inhibition of cell proliferation and induction of apoptosis in 3 CRC cell lines treated with 3 concentrations of metformin (1, 5, and 10 mmol/L) [32].…”
Section: Cell Line Studiesmentioning
confidence: 67%
“…In order to inhibit mitochondrial complex I and consequently decrease tumorigenesis, cancer cells need a robust inner mitochondrial membrane potential to allow metformin to reach the mitochondrial matrix. It is therefore possible to hypothesize that metformin efficacy as an anticancer agent depends on the tumor expression of OCTs and a recent work [ 83 ] has shown that the selectivity of metformin response may be due to hormonal, metabolic, and associated genetic factors, including some allelic polymorphisms related to OCTs. Moreover, cancer heterogeneity of OCT1, and hence for cancer cell uptake of metformin, could be assessed before considering metformin therapy in the clinical and prevention setting given, for example, the low expression of OCT1 in normal breast tissues.…”
Section: Action Of Metformin On Mitochondrial Activitymentioning
confidence: 99%
“…В случае последних речь идет преимущественно о полиморфных вариантах генов, кодирующих белки, ассоциированные с утилизацией/ метаболизмом метформина и механизмом его действия (см. более подробно в работах [8,9] и ниже). В отношении предикторов возможного противоопухолевого действия метформина (в особенности, в том случае, когда опухо-левая ткань для анализа недоступна) вопрос находится на достаточно ранней стадии своего изучения [9,10].…”
Section: /2014unclassified
“…ДНК выделяли соль-хлороформным методом, генотипирование проводили при помощи ал-лель-специфической полимеразной цепной реакции (ПЦР) в режиме реального времени на приборе iQ iCycler (Bio-Rad) с использованием интеркалирующего краси-теля SYBR Green I. Праймеры, их температуры отжига и длины синтезированных фрагментов для анализа по-лиморфизма соответствующих генов приведены в ра-боте [9]. ПЦР-амплификация проходила в объеме 20 …”
Section: генотипированиеunclassified
See 1 more Smart Citation